2017
DOI: 10.1088/2053-1583/aa61e5
|View full text |Cite
|
Sign up to set email alerts
|

The normal-auxeticity mechanical phase transition in graphene

Abstract: When a solid object is stretched, in general, it shrinks transversely. However, the abnormal ones are auxetic, which exhibit lateral expansion, or negative Poisson ratio. While graphene is a paradigm 2D material, surprisingly, graphene converts from normal to auxetic at certain strains. Here, we show via molecular dynamics simulations that the normal-auxeticity mechanical phase transition only occurs in uniaxial tension along the armchair direction or the nearest neighbor direction. Such a characteristic persi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 33 publications
2
44
0
Order By: Relevance
“…The Young's modulus of ingredient B has no effect on the results of k n and α n , but strongly affects the stiffness of the cellular materials. The normal‐auxeticity mechanical phase transition has recently been found in graphene, an atomic‐thick 2D hexagonal carbon . The results in this paper could apply to multiscale metamaterials design spanning from macro‐ down to micro‐ and nanoscales and our study opens a new avenue to developing more sensitive functional materials or devices.…”
supporting
confidence: 54%
“…The Young's modulus of ingredient B has no effect on the results of k n and α n , but strongly affects the stiffness of the cellular materials. The normal‐auxeticity mechanical phase transition has recently been found in graphene, an atomic‐thick 2D hexagonal carbon . The results in this paper could apply to multiscale metamaterials design spanning from macro‐ down to micro‐ and nanoscales and our study opens a new avenue to developing more sensitive functional materials or devices.…”
supporting
confidence: 54%
“…To adopt the AIREBO potential for large deformation, researchers generally modify the cutoff distances according to the specific systems studied [18,19,20]. We have examined this r min cc parameter and adopted the value of 1.92Å, as reported in our previous work [14]. The stress-strain curves are extremely insensitive to the cutoff distances under the strain below 0.1.…”
Section: Simulation Methodsmentioning
confidence: 99%
“…Considering that the graphene, a honeycomb like structure, has a rotational symmetry in the plane and there is only 30 • apart between the armchair direction and the closest zigzag direction, we hypothesize that the anisotropy of the NA transition might imply a possible critical stretching direction between the armchair and the zigzag direction with respect to this NA transition phenomenon. To explore this issue, we have carried out extensive studies by taking advantage of our previous work [14], and shown that the NA transition disappears at a magic angle θ (shown in Figure 1) of around 10.9 • and this magic angle is weakly dependent on the temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The Brenner second-generation reactive empirical bond-order potential [24,25] was used to model the C-C bounded interaction, while the Fe-Fe and Fe-C interactions were modeled with the embedded atom potential [26]. The embedded atom potential is described by two terms [27]:…”
Section: Model Setup and Interatomic Potentialmentioning
confidence: 99%